UPAYA GURU DALAM MENINGKATKAN ASPEK PSIKOMOTORIK SISWA MELALUI MEDIA AUDIO VISUAL DI KELAS IV SEKOLAH DASAR NEGERI 18 SADAYAN TAHUN PELAJARAN 2021- 2022 - Nurhaliza, Nurhaliza; Suhari, Suhari; Syafiudin, Syafiudin (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2025)
This research was conducted because there are a number of interesting things about the way teachers in improving the psychomotoraspects of student conducted in class IV SDN 18 Sadayan includingsome students look passive, not enthusiastic and less enthusiastic in participating in learning in class that indicates the weak motivation of learning in students. With this situation, class IV teachers have a fairly effective way to foster student motivation by using audio visual media in the form of infocus in the learning process. The purpose of this study is to reveal what the teachers’ efforts are in improving the psychomotor aspects of student in class IV through audio visual media. This study uses a phenomenological approach whit qualitative research types. The results of this study: first, class teachers conduct learning using learning media, which is in the form of audio visual electronic media such as the use of infocus in displaying learning videos assisted with loudspeakers. Second, the teacher adjusts the learning media to be used with the material to be taught. Learning media that will be used must be practical and interesting so that student more easily understand and are interested in participating in classroom learning. Three, the teacher is selective in determining the media to be used. Because in the selection of the media it is necessary to compatibility or compatibility with the material to be delivered. So that when learning takes place students not only focus on the material but can also enjoy the course of the learning process in the classroom.